2007
DOI: 10.1002/pmic.200601045
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis associated with term placental insufficiency in cloned pig

Abstract: Somatic cell-derived nuclear transfer (scNT) is a method of animal cloning in which the oocyte reprograms a somatic cell nucleus to divide and execute developmental programs. Despite many successes in this field, cloning by scNT remains very inefficient. Unlike other cloned animals, pigs derived by scNT have placentas with severe villous hypoplasia. To obtain a better understanding of the protein networks involved in this phenomenon, we assessed global protein expression profiles in term placentas from scNT-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 44 publications
5
53
0
Order By: Relevance
“…Histological analyses of 28 of the 38 scNT clones that died after birth revealed 11 had distinct histological anomalies, the most common of which was meningitis, followed by poor development of the elbow joint bone, flexor tendons, congestion, and Leydig cell hypoplasia (Park et al, 2004(Park et al, , 2005. As shown in our very recent report, the abnormal histopathologic findings of the deceased cloned pigs are closely associated with aberrant protein expression patterns (Park et al, 2005;Chae et al, 2006;Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Histological analyses of 28 of the 38 scNT clones that died after birth revealed 11 had distinct histological anomalies, the most common of which was meningitis, followed by poor development of the elbow joint bone, flexor tendons, congestion, and Leydig cell hypoplasia (Park et al, 2004(Park et al, , 2005. As shown in our very recent report, the abnormal histopathologic findings of the deceased cloned pigs are closely associated with aberrant protein expression patterns (Park et al, 2005;Chae et al, 2006;Lee et al, 2007).…”
Section: Discussionmentioning
confidence: 56%
“…This finding is in part because of a high incidence of fetal death that is due to a variety of afflictions during pregnancy, including fetal overgrowth and placental malformations (Hiendleder et al, 2004;Arnold et al, 2006;Chae et al, 2006;Lee et al, 2007). These studies have revealed that some of the subtle abnormalities of adult scNT-derived animals are species-specific.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many abnormalities observed in SCNT fetuses and offspring may be influenced by deficiencies in mitochondrial function. Recently, comparative proteomic analyses of SCNT piglets and placentae from SCNT pigs were reported [18][19][20]35]. Two-dimensional gel electrophoresis analysis revealed changes in the responses of several detoxification-related proteins to stress and inflammation in sudden death observed in SCNT piglets with extensive hepatopneumonic apoptosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional gel electrophoresis analysis revealed changes in the responses of several detoxification-related proteins to stress and inflammation in sudden death observed in SCNT piglets with extensive hepatopneumonic apoptosis [17]. Lee et al [18] assessed the global protein expression profiles in term placentas from SCNT pigs and found that the proteins closely involved in the apoptotic signaling pathway were different in comparison with controls. In malformed umbilical cords of SCNT piglets, proteins prevention of oxidative stress were downregulated, while molecules involved in apoptosis were upregulated [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation